Parental Stress in Parents of Children with Learning Disabilities: A Limited Demographic Factors - Kamaruddin, Kamarulzaman; Abdullah, Che Anuar Che; Idris, Mohd Noor (International Review of Management and Marketing, 2016)
The main purpose of this study was to examine the level of stress among the parents of children with learning disabilities (LD children). The data were obtained from a survey using the Perceived Stress Scale that involves 264 parents. The results revealed that a total of 99 (37.6%) parents experiencing stress at low level (M = 1.00 – 2.33) and they were in the state of normal. Whilst 138 (52.3%) of the parents were suffering moderate level of stress (M = 2.34 – 3.66) which is considered as mild. Furthermore, the analysis indicated that only 27 (10.1%) of them experienced high level of stress (M = 3.67 – 5.00) which is classified as severe. The findings indicated that mothers of LD children was associated with higher stress and were significantly experienced more stress than fathers. In terms of ethnicity, the findings showed that Chinese parents are experiencing more stress than the Malay and Indian parents. Accordingly, parents of high SES were reported experiencing greater stress than parents of middle and low SES. In contrast to the findings on parents of different religious groups whereby they were at moderate level of stress and the result also showed that there is no significant difference between the Muslims, Christians, Buddhists and Hindus with regard to parenting stress. Keywords: Stress, LD children, Ethnic JEL Classifications: C610, C623, I23